Crisis of Leadership in a Fast Changing Digital World - Dr. K. R. Subramanian, (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
By 2050 world population could be around 9 billion people - to feed, clothe, transport, employ and educate. With our commitment to a growthdriven world economy that will face inflation, supply endless consumption to everyone, we add a digital device everyday that helps everyone to succeed and prosper. We have reached greatness, no doubt, but our magnificent successes will be matched by the growing Crisis of Success. As we pursue unlimited growth, our endless consumption threatens to warm the climate, overspending of our financial resources, requiring more fresh water than we have, increasing income inequality, diminishing other species and triggering shock waves whenever we are unable to cope with a problem. Billions of people are at the “bottom” of the economy. The middle class is becoming irrelevant in advanced societies. Many no longer believe today’s leaders can improve this, though they are increasing their power and digital devices. Leaders want new options as much as everyone else. Apparently, there is room to dream about a more successful world along with new technology. The big questions are: Can we envision a world where tech helps everyone succeed and prosper? Can that world be designed and built now, without waiting for “the future” to arrive?